TEKNIK PENYISIPAN PADA DATA DIGITAL DENGAN MENGGUNAKAN METODE LEAST SIGNIFICANT BIT - Margiutomo, Sapta Aji Sri (DINAMIKA DOTCOM, 2011)
Changes in the presentation of data from analog to digital turned out to bring the issue of copyright protection and authentication for digital image.Â  This is due to the ease with which duplicates can be made to the digital image.Digital watermaking can be applied to insert a copyright label into a digital image of the invisible. This will be difficult for an unauthorized person to remove the copyright label so that only authorized parties are able to reveal the label copyright. The method used is the method of LSB (Least Significant Bit).Â Keywords : Digital Watermaking, LSB